Improving Speaking Skill through Peer Tutoring Strategy to Members of An English Meeting Club - Alim Akkas (LETS: Journal of Linguistics and English Teaching Studies, 2020)
English speaking skill helps people to communicate and interact with other people. The objective of the research is to know whether peer tutoring strategy is able to or not to improve the speaking skill of members of YEMC of MTs YMPI Rappang in learning speaking through peer tutoring strategy. This research used pre-experimental method by one group pre-test post-test design. The population was the members of YMEC of MTs YMPI Rappang. The sample of this research was 20 members. The technique of sampling was total sampling technique. The data was analyzed by using SPSS version 17 computer software and the second question was analyzed by using questionnaire. The result calculation of mean score pre-test of students was 7, and mean score post-test of students was 10,35. It showed that members' seapking skill was improved. The result finding that SPSS output for paired sample t-test= 11,513 and sig (2-tailed) = 0,000. This out reveals that sig= 0,000 was lower p-value= 0,05. It showed the alternative hypothesis (Ha) is accepted, which t-test value (11,513)was greater than t-table value (2,093). Based on data analysis, the researcher concluded that through peer tutoring strategy can improve the speaking skills at members of YEMC of MTs YMPI Rappang. Based on the calculation, peer tutoring strategy has a very strong influence to improve the members speaking skill.